Stratigraphy of the Ransi Member of the Middle Eocene to Oligocene Tatau Formation in the Tatau-Bintulu area, Sarawak, East Malaysia / Wong Yien Lim - Wong, Yien Lim (2012)
A recent study in the Tatau-Bintulu area indicates that the Ransi Member which was originally dated as Upper Miocene to Pliocene (Kamaludin Hassan, 2004) is part of the Upper Eocene to Upper Oligocene Tatau Formation. This finding is inconsistent with that of Liechti, et.al (1960) who proposed that it was equivalent to the Middle to Upper Miocene Begrih Formation while Ismail (2000) proposed that it was equivalent to the Upper Miocene to Pliocene Balingian Formation. The study area is located in a horst bounded by two parallel NE-SW trending faults 4.5 km apart. The gently folded Ransi Member that is located at the base of the Tatau Formation, sits above an angular unconformity that separates it from the underlying more tightly folded Belaga Formation. The Ransi Member is made up of mostly thick bedded conglomerate and sandstone interbedded with thin shale horizons. The conglomerate in Tutong Hill, Tatau Hill and Ransi Hill are mainly composed of pebbles of angular to sub-angular clasts of chert, quartz, igneous and metamorphic fragments. The igneous clasts are composed of rhyolite similar to that in the Middle Eocene igneous intrusion at Bukit Piring in the Tatau Area. A very thick black carbonaceous horizon was found at the Hormat Pacific Quarry, to the northeastern part of Tatau Hill. Vitrinite reflectance from the coal of Ransi Member is similar to the Tatau Formation, it is higher than the Vitrinite Reflection of Nyalau and Balingian Formations but lower than Belaga Formation. Cross-bedded sandstone channels are dominant in the Ransi Member. Rounded to sub-rounded cobbles and boulders of soft sandstone and slumped features are found in the Pelungau area indicating a different source and depositional conditions that distinguishes it from the Ransi Member. The Pelungau Conglomerate is a local event that occurs within Tatau Formation that might have been triggered by faults. The discovery of significant burrowing in many sandstone beds within the upper part of the Ransi Member together with marine microfossils in the shale beds suggest that the fluvial channels in a lower coastal plain environment was gradually replaced by a more shallow marine environment indicative of a marine transgression. The source of the Ransi beds was largely from the radiolarian rich chert and metamorphic rocks of the older Rajang Group located to the south as indicated by paleocurrent determinations. The presence of volcanic clasts in the conglomerate from Tatau Hill suggests a volcanic source in the hinterland during the deposition of the Ransi beds. The gently folded Arip Limestone is a shallow marine deposit equivalent to or younger than the Ransi Member found within the Tatau Formation to the southwest of the area. Microfosils such as Globigerinatheca sp. in the Arip Limestone extends the age down to Middle Eocene from Late Eocene previously (Leitchi et al, 1960) for the base of the Tatau Formation. If it is younger than the Ransi and the Ransi is at the base of the Tatau Formation, than the Ransi’s age could be older than Middle Eocene.